Nivolumab-refractory patients with advanced non-small-cell lung cancer. (April 2019) - Costantini, A.; Fallet, V.; Corny, J.; Friard, S.; Chouaid, C.; Duchemann, B.; Giroux-Leprieur, E.; Taillade, L.; Doucet, L.; Brosseau, S.; Wislez, M.; Tredaniel, J.; et al.
Highlights: Hyper progressive disease is a new form of progression in patients treated with immunotherapy. The definition of HPD is yet to be consensual. We suggest a clinical definition of patients refractory to immunotherapy based on the number of nivolumab injections. 20% of patients with advanced NSCLC presented with nivolumab refractory disease in our real-life cohort. Factors associated with refractory disease were PS ≥ 2, shorter duration of treatment before nivolumab initiation. Abstract: Introduction: : Immune checkpoint inhibitors (ICIs) have revolutionised cancer care especially in lung cancer. New response patterns have been described under ICIs such as pseudo-progression or hyper-progressive disease (HPD). The definition of HPD is yet to be consensual. The aim of this study was to suggest a clinical definition of nivolumab-refractory patients and find factors associated with this entity. Methods: : We performed a multi centric retrospective study including all patients who received nivolumab for the treatment of advanced non-small cell lung cancer (NSCLC) during the French authorisation for temporary use in 2015. Results: : 303 patients were included in the cohort and 292 had details on the number of nivolumab injections received. 57 patients (20%) were nivolumab-refractory. These patients had worse PS at nivolumab initiation (p < 0.0001), shorter duration of treatment before nivolumab (p = 0.028) and had dramatically shorter nivolumab overall survival (p < 0.0001) than patients who did not present with refractory disease. Conclusion: : Nivolumab-refractory disease can affect up to 20% of patients treated with nivolumab for advanced NSCLC with dramatically shortened survival rates. Further studies are needed to understand the precise mechanisms leading to refractory disease as well as its management.